Luxembourg : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Luxembourg. (IMF Staff Country Reports; Country Report, 2021)
The economic impact of the pandemic has been much milder than initially foreseen, still the outlook remains challenging. The economy, dominated by financial services, adapted quickly to telework and benefited from unprecedented policy support, both domestically and globally. Uncertainty is unusually high, dominated by the virus dynamics in the short term, with downside risks relating to a sharp rise in global risk premia, deglobalization trends, and changes in international taxation.